Antioxidant Activity of Sprouting Mungbean (Vigna radiata) Variety VIMA-1 - Puyanda, Irvia Resti; Kuswanto, Kapti Rahayu; Margareta, Laurensia Atha; Anggraini, Metha Putri Agustyn (Journal of Applied Food Technology, 2022)
The  objectives  of  this  work  were  to  investigate  the  influence  of  germination times (24, 48, 72, 96, and 120 hours) and conditions (light and dark conditions) on the antioxidant activity and total phenolic compounds in mungbean sprout. Antioxidant  activity and  total  phenolic  content  were  analyzed  using  in  vitro methods,  with  the  antioxidant  activity  assessed  using  ABTS  and  DPPH methods. We observed a significant increase (p < 0.05)  in antioxidant activity using  the  ABTS  method,  which  decreased  after  48  hours  of  germination.  In contrast, the DPPH method showed a significant decrease (p < 0.05) followed by an increase in antioxidant activity after 48 hours of germination. Meanwhile, germination up to 48 hours significantly reduced (p < 0.05) the total phenoliccontent in both conditions, while against that time, it increased significantly (p <  0.05)  up  to  96  hours.  The  effects  of  germination  time  and  conditions  were significant (p < 0.05) for both antioxidant activities and total phenolic content. Generally,  germination  under  dark  conditions  resulted  in  lower  antioxidant activities and total phenolic content during the germination process